Effect of additives on the dynamic bubble growth behavior of polymer foam evaluated with in-situ visualizations and simulations. (January 2022) - Hu, Dongdong; Gao, Xiulu; Qiang, Wei; Chen, Yichong; Xu, Zhimei; Zhao, Ling
Abstract: Effect of CO2 -philic additive additives PDMS and co-blowing agent alcohol on dynamic bubble growth behavior of supercritical CO2 assisted polymer foaming process, was investigated by using a visual observation system combined with numeric model. The addition of PDMS in PS accelerates the bubble nucleation and growth rate, and the bubble growth rate decreases with the increase of PDMS molecular weight. The bubble growth of polymer is mainly determined by the effect of PDMS on the solubility and diffusion of CO2, and the bubble growth model has a good agreement with the experimental values. When using alcohols as co-blowing agents, 1-butanol and 1-hexanol accelerates the bubble growth rate owing to the strong plasticizing effect on PS, resulting that the predicted bubble growth rate and bubble diameter has a deviation with the experimental data. Alcohol significantly decreased the diffusion coefficient of blowing agent, the bubble growth is controlled collectively by the dissolution and diffusion of blowing agent and the viscosity of polymer matrix after plasticizing. Graphical abstract: Image 1 Highlights: Visualization system combined with the numerical model was applied to analyze bubble growth of PS/additives. CO2 -philic additives change dissolution and diffusion of CO2 in PS which has a significant effect on bubble growth behavior. Variation of bubble size over time in PS/PDMS system obtained by visualization has a good agreement with numerical model. Alcohol decreased the diffusion coefficient of CO2, so that the bubble growth becomes a diffusion controlled process.